A new species of Rhinella (Anura: Bufonidae) from Brazilian Amazon - Lima, Albertina P.; Menin, Marcelo; de Araújo, Maria Carmozina (Zootaxa, 2007)
We describe adults, tadpoles, advertisement calls and provide information about natural history of a new species of toad in the Rhinella margaritifera species group from Pará, Brazil. The new species is characterized by medium size, snout pointed in dorsal view, supraorbital and supratympanic crests continuous, both with tubercles, tympanic membrane distinct, bony protusion at angle of jaws, parotoid glands small and not very distinct, lateral row of tubercles present, neural crests of vertebrae absent, skin on dorsal and dorsolateral surfaces with spicules in males and females. This species differs from other described species in the Rhinella margaritifera group also in tadpole morphology, acoustic characteristics and reproductive behaviour.